The Overview of Dengue Hemorrhagic Fever Based on Larva Free Index, Education Level, and Population Density - Afifah Afifah; Rudi Fakhriadi; Ratna Setyaningrum; Musafaah Musafaah; Dian Rosadi (Jurnal Berkala Kesehatan, 2021)
One of the diseases that still has the potential to become an epidemic in Indonesia is Dengue Hemorrhagic Fever (DHF). Banjarbaru City is a dengue-endemic area with a high number of new cases (IR) of dengue during 2016-2018 consecutively. In 2018, Banjarbaru City's IR DBD was the second highest after Hulu Sungai Selatan Regency at 105.24 per 100,000 population. The purpose of this study is to describe the incidence of dengue hemorrhagic fever based on the review of larva free index, education level, and population density in the City of Banjarbaru in 2018-2019. The population in this study is demographic data and health data in the City of Banjarbaru in 2018-2019. The sample of this research is the data on dengue cases, larva free index data, education level data, and population density data for the City of Banjarbaru in 2018-2019. Descriptive data analysis used frequency distribution tables and cross-tabulations. The results showed descriptively low larva free index showed a low incidence of DHF (2018 (18.75%) 2019 (11.11%), high levels of education showed a high incidence of DHF (2018 (20%), 2019 (20%), and high density indicates a high incidence of DHF (2018 (18.75%) in 2019 (12.5%).